2020
DOI: 10.1111/bph.14962
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anti‐VEGF and kinin B1 receptor blockade on retinal inflammation in laser‐induced choroidal neovascularization

Abstract: Background and Purpose: Age-related macular degeneration (AMD) is a complex neurodegenerative disease treated by anti-VEGF intravitreal injections. As inflammation is potentially involved in retinal degeneration, the pro-inflammatory kallikreinkinin system is a possible alternative pharmacological target. Here, we investigated the effects of anti-VEGF and anti-B 1 receptor treatments on the inflammatory mechanisms in a rat model of choroidal neovascularization (CNV). Experimental Approach: Immediately after la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 89 publications
8
28
0
1
Order By: Relevance
“…B1R antagonism or deletion plays a protective role in inflammation, organ damage, and lethal thrombosis in septic shock in diabetes [53]; lipopolysaccharide (LPS) mediated acute renal inflammation [54]; renal ischemia-reperfusion injury [55]; and in cardiovascular [56] and retinal [57][58][59][60] inflammatory diseases. B1R inhibition reversed vascular [61] and retinal [58,60] inflammation induced by diabetes mellitus.…”
Section: Kinin Receptors In Inflammation and Neovascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…B1R antagonism or deletion plays a protective role in inflammation, organ damage, and lethal thrombosis in septic shock in diabetes [53]; lipopolysaccharide (LPS) mediated acute renal inflammation [54]; renal ischemia-reperfusion injury [55]; and in cardiovascular [56] and retinal [57][58][59][60] inflammatory diseases. B1R inhibition reversed vascular [61] and retinal [58,60] inflammation induced by diabetes mellitus.…”
Section: Kinin Receptors In Inflammation and Neovascularizationmentioning
confidence: 99%
“…Similarly to other organs, the KKS in the eye is a double-edged sword, as it contributes to many physiological processes including blood-flow regulation and vascular tone control, but also partakes in the complex processes of inflammation [4,57,89]. It was reported that the KKS underlies a number of ocular pathologies (DR, AMD, choroidal neovascularization, macular edema) associated with inflammation and pathological neovascularization, particularly in the human and rat retina [57][58][59][60]69,[90][91][92][93]. For instance, PK and HK, by binding to the vascular endothelium, release BK and subsequently activate B2R, which plays a key role in the control of vascular tone [4].…”
Section: Kallikrein-kinin System In the Eyementioning
confidence: 99%
“…Among them, ophthalmologic antioxidant cocktails (e.g., vitamins 21 , lutein and zeaxanthin 22 ) have been applied to protect retinal cells from oxidative damage, yet the therapeutic outcomes are unsatisfactory due to the unfriendly schedule and underlying biosafety concerns (such as potential risks of skin rashes 23 , haemorrhagic stroke 24 and lung cancer in cigarette smokers 25 ). Injection of anti-VEGF agents, including ranibizumab 26 , aflibercept 27 and bevacizumab 28 , which bind to the VEGF receptors to block VEGF, is mainly used to treat wet AMD 29 via inhibition of choroidal neovascularisation 30 . However, adverse reactions of the eyes (such as endophthalmitis, uveitis, retina split holes and vitreous haemorrhage) and systemic adverse reactions (such as hypertension, myocardial infarction and stroke) caused by frequent intravitreal injections and the high cost of treatment lead to poor patient compliance and compromised effectiveness 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-VEGF therapy is considered to be one of the most effective treatment options for DR and wet-AMD and is frequently used off label to treat ROP [11][12][13][14][15]. Current FDA approved anti-VEGF agents include bevacizumab, ranibizumab, and aflibercept, which are administered via monthly or bi-weekly intravitreal injections [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%